Negotiating Religious Moderation and Legal Pluralism in Indonesia: A Socio-Anthropological Perspective - Yazwardi, Yazwardi; -, sandy wijaya; Erniwati, Erniwati (KURIOSITAS: Media Komunikasi Sosial dan Keagamaan, 2025)
Tensions between religious communities in a nation become one of the triggers of social conflicts that result in communal conflicts based on ethnicity, religion, race, and intergroup. Communal conflict is a very crucial social issue because it can trigger a civil war that takes many victims. Communal conflict factors are generally preceded by social prejudice that makes a person or group of people deny the existence of equality and equal rights. Cases of social prejudice often arise more because of religious sentiment and sectarian politics, and or other identity politics. An understanding of religious moderation is a strong indicator for realizing social harmony in the life of pluralistic Indonesian society. Indonesia is a state of law that also embraces legal pluralism in certain legal rules. The level of understanding of religious moderation that is symmetrically related to legal pluralism becomes a problem in this paper. This research is based on quantitative research. Primary data is used to determine the level of understanding (perception) of religious moderation among religious leaders and officials in South Sumatra Province. Primary data were obtained through a questionnaire based on GoogleForm online. The focus and location of the research is Palembang City which represents the highest level of heterogeneity compared to other regions in South Sumatra Province. Based on data analysis, it was found that the level of understanding of religious moderation is very high, while the level of understanding of the manifestation of legal pluralism is below the level of high. It is recommended that there is a public policy in which there is a legal policy of the Regional Government through Regional Regulations to realize religious moderation by increasing public knowledge through religious moderation education and the ability to understand legal pluralism which is a necessity in the Unitary State of the Republic of Indonesia. For the Central Government, it can issue legal products in the form of laws or other regulations on religious moderation and legal pluralism.